Ion upflow dependence on ionospheric density and solar photoionization. Issue 11 (21st November 2015) - Cohen, I. J.; Lessard, M. R.; Varney, R. H.; Oksavik, K.; Zettergren, M.; Lynch, K. A.
Abstract: Motivated by rocket observations showing a variety of different ionospheric responses to precipitation, this paper explores the influence of the background ionospheric density on upflow resulting from auroral precipitation. Simulations of upflow driven by auroral precipitation were conducted using a version of the Varney et al. (2014) model driven by precipitation characterized by observations made during the 2012 Magnetosphere‐Ionosphere Coupling in the Alfvén resonator rocket mission and using a variety of different initial electron density profiles. The simulation results show that increased initial density before the onset of precipitation leads to smaller electron temperature increases, longer ionospheric heating timescales, weaker ambipolar electric fields, lower upflow speeds, and longer upflow timescales but larger upflow fluxes. The upflow flux can increase even when the ambipolar electric field strength decreases due to the larger number of ions that are accelerated. Long‐term observations from the European Incoherent Scatter (EISCAT) Svalbard radar taken during the International Polar Year support the effects seen in the simulations. This correlation between ionospheric density and ion upflows emphasizes the important role of photoionization from solar ultraviolet radiation, which the EISCAT observations show can increase ionospheric density by as much as an order of magnitude during the summer months. Key Points: Simulations show that ionospheric density affects several aspects of ion upflow EISCAT radar observations support new simulation predictions of ionospheric density on ion upflow EISCAT observations show the seasonal variation in ionospheric density due to solar photoionization